Drug-coated balloons are not inferior to drug-coated stents in the treatment of acute myocardial infarction and shorten the duration of dual antiplatelet treatment - Jing Yang; Shuting Chang; Jing Liu; Guanzhao Zhang; Yue Wang; Baixue Zhang; Zifan Nie; Yuanbao Dong; Bo Li (Emergency and Critical Care Medicine)
Abstract. Background. Drug-coated balloons (DCBs) are an up-and-coming tactic in treating in-stent restenosis and coronary artery small vessel disease, but their efficacy in treating acute myocardial infarction needs to be further explored. Methods. A meta-analysis of 7 studies was conducted to make a comparison with the results of DCB and drug-eluting stent implantation after a median follow-up of 15 months. Results. A total of 922 patients were included in this analysis in total, including 375 patients in the DCB group and 547 patients in the stent group. A total of 962 vascular diseases were manifested in the 2 groups. After 6 to 24 months of follow-up, there was no statistically significant difference with respect to major adverse cardiovascular events (odds ratio [OR]: 0.82; 95% confidence interval [CI]: 0.52–1.29; Z = 0.85; P = 0.39), cardiac death (OR: 0.92; 95% CI: 0.39–2.12; Z = 0.21; P = 0.84), target lesion revascularization (OR: 1.09; 95% CI: 0.53–2.25; Z = 0.24; P = 0.81), late lumen loss (MD: −0.05; 95% CI: −0.15 to 0.06; Z = 0.85; P = 0.40), or dual antiplatelet therapy (DAPT) (OR: 1.04; 95% CI: 0.53–2.05; Z = 0.11; P = 0.91) between the 2 groups. In the DCB group, persistent residual stenosis or C-F dissection occurrence necessitated that a total of 30 patients receive extra bailout implantations. The rate of bailout stenting was 11.8% (95% CI: 7.1–16). Moreover, the DCB group had a shorter DAPT duration compared with the stent group. Conclusion. Drug-coated balloons with shorter DAPT durations may be as effective and safe as stent therapy in treating acute myocardial infarction.